Geodetic projects as part of Main project for new basic leveling network - Zlatko Srbinoski; Zlatko Bogdanovski (Faculty of civil engineering - Skopje, 2017)
The basic leveling network is a part of geodetic networks, with which is defining altimetric base for performing of the geodetic activities within a state. In time period 2011-2013, an extensive preparations and specific field activities were carried out for realization of a new basic level network. With new leveling network the state it’s trying to deflect the short comings of the existing leveling network, as well as to realize its intentions to connect its geodetic networks in frame of the European geodetic networks. In this paper are shown the short history of leveling networks in Republic of Macedonia, the concept and main characteristics of new leveling network, as well as results of the leveling measurements.
Keywords: basic leveling networks, geodetic networks, leveling network